2021
DOI: 10.1111/jocs.15943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute normovolemic hemodilution on post‐cardiopulmonary bypass coagulation tests and allogeneic blood transfusion in thoracic aortic repair surgery: An observational cohort study

Abstract: Background and Aim Perioperative blood transfusion is associated with increased morbidity and mortality. Acute normovolemic hemodilution (ANH) is a blood conservation strategy associated with variable success, and rarely studied in more complex cardiac procedures. The study aim was to evaluate whether ANH improves coagulopathy and reduces blood transfusions in thoracic aortic surgeries. Methods Single‐center observational cohort study comparing ANH and standard institutional practice in patients who underwent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The amount of blood removed depends on various factors such as baseline Hb concentration, expected blood loss and haemodynamic stability. The use of the technique of ANH has been shown to reduce transfusion of allogeneic blood products 399–403 . Benefits of ANH include decreasing Hb concentration during the period when most surgical blood loss is occurring, thereby minimising the effects of loss of RBCs; re-infusing the patient's own fresh whole blood containing RBCs, platelets and clotting factors when it is needed during or shortly after the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of blood removed depends on various factors such as baseline Hb concentration, expected blood loss and haemodynamic stability. The use of the technique of ANH has been shown to reduce transfusion of allogeneic blood products 399–403 . Benefits of ANH include decreasing Hb concentration during the period when most surgical blood loss is occurring, thereby minimising the effects of loss of RBCs; re-infusing the patient's own fresh whole blood containing RBCs, platelets and clotting factors when it is needed during or shortly after the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the technique of ANH has been shown to reduce transfusion of allogeneic blood products. [399][400][401][402][403] Benefits of ANH include decreasing Hb concentration during the period when most surgical blood loss is occurring, thereby minimising the effects of loss of RBCs; reinfusing the patient's own fresh whole blood containing RBCs, platelets and clotting factors when it is needed during or shortly after the surgical procedure. In cardiac surgical patients with normal to high initial Hb concentrations, a decreased blood viscosity because of ANH may have cardioprotective effects.…”
Section: Cytokine Removalmentioning
confidence: 99%
“…For example, ANH reportedly improved the aPTT and fibrinogen levels slightly in cardiac surgery under CPB [ 3 ]. In thoracic aortic surgery, ANH improved the PT-INR, platelet count, and fibrinogen levels and reduced the transfusion of fresh frozen plasma and platelet concentrate [ 15 ]. Another study demonstrated the hemostatic effect of ANH on cardiac surgery under CPB [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important part of the blood conservation strategy and clotting preservation. 92,93 The pump prime can be done with crystalloid or colloids (i.e., human albumin). While leading PEA centers differ in the priming methods, mortality outcomes are similar.…”
Section: Surgery and Deep Hypothermic Circulatory Arrestmentioning
confidence: 99%